Carbon Price Evaluation in Power Systems for Flaring Mitigation - Tovar-Facio, Javier; Fuentes-Cortes, Luis F.; Ponce-Ortega, José M. (Journal of Sustainable Development of Energy, Water and Environment Systems, 2019)
This work aims to study the effect of greenhouse gases monetization to promote the reduction of flare gas. We propose to design a cogeneration system that uses natural gas as main fuel and flare gas as complementary fuel. A multi-objective nonlinear programming model is presented to determine the optimal design variables of the cogeneration system. This model maximizes the profit and minimizes the carbon dioxide equivalent simultaneously. The key factor to minimize carbon dioxide emissions is the replacement of natural gas with flare gas. Three different cases, which consider different methods to sponsor flare gas, are compared. The first case seeks to maximize the profit with trading carbon emissions. The second case also looks for maximizing the profit, however, carbon dioxide emissions are penalized by carbon taxes. In the third case, a multi-objective optimization approach based on a compromise solution that balances conflicting priorities on multiple objectives is presented. Results show that these two policy schemes work with some limitations to decrease carbon dioxide emissions. On the other hand, when the approach based on a compromise solution is used, the results show, at the same time, environmental and economic benefits.